Prevalence and determinants of motorcycle safety helmet usage among Tamil primary school students in Hulu Langat district, Malaysia - Aramugam, Tamil Selvi (2021)
In 2018, globally the numbers of people who are being killed in road traffic crashes are 1.35 million. Road traffic injuries are being the 8th leading cause of death among the people of all ages. It is also number one cause of death among children and young adults aged five to twenty-nine years old. Head injuries are known to be the leading cause of death and major trauma. The risk of fatal injuries can be reduced up to 42% if the motorcycle helmet is correctly worn. Meanwhile, the risk of head injuries can be reduced up to 69% with the correct usage of motorcycle helmet. The aim of this study is to measure the prevalence and predictors of motorcycle safety helmet usage among Tamil primary school students. Design: A cross sectional study design. Location: Hulu Langat district, Selangor. Participants: 222 students from 7 Tamil primary schools in Hulu Langat district were included in the study via simple random sampling method. The guardians as well as the child pillion riders were observed on motorcycle helmet usage and recorded in the observational sheet. The guardians answered the questionnaire providing info pertaining to their children upon signing the consent form. Statistical Analysis: The collected data was analyzed using International Business Machine Statistical Package for Social Sciences Version 21 (IBM SPSS). Descriptive analysis, Chi-square or Fisher’s Exact test and Logistic regression analysis were used to obtain the statistical result. A total of 222 students participated in this study with 87.7% of response rate. 18% of the child pillion riders and 75.2% of the riders were observed using motorcycle helmet while travelling by motorcycle. The result showed that pillion riders with female riders, travelling as one pillion rider, those who are travelling to urban area schools and those with riders owns a motorcycle riding license uses motorcycle helmet more. In conclusion, the percentage of motorcycle helmet usage among the Tamil primary school students in Hulu Langat district was poor compared to the motorcycle riders. Therefore, it seems to be a major problem. To overcome this, the awareness programs should target male parents who are travelling with more than one pillion rider with lower family income and from rural area especially those without license.